PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ANIMASI INTERAKTIF TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effect of the Problem Based Learning (PBL) model assisted by interactive animation media on students’ mathematical conceptual understanding and compares it with conventional learning methods. An experimental research method with a control group pretest–posttest design was employed. The sample consisted of two classes of grade XI students at SMKS Al-Washliyah Pasar Senen 2 Medan in the 2025/2026 academic year. Class XI TKJ, consisting of 36 students, was assigned as the experimental group and received instruction using the PBL model assisted by interactive animation media. Class XI TBSM, consisting of 32 students, served as the control group and was taught using conventional learning methods. The research instrument was a mathematical conceptual understanding test administered as both a pretest and a posttest to measure students’ initial and final understanding. The results showed that the experimental class achieved a higher average posttest score of 82.40 compared to the control class, which obtained an average score of 73.38. The mean difference between the two classes was 9.02 points. Statistical analysis using the Independent Samples t-test indicated a significance value (2-tailed) of 0.000, which is less than 0.05, with a t-value of 6.075. These findings indicate that the PBL model assisted by interactive animation media has a significant positive effect on students’ mathematical conceptual understanding. Moreover, there are significant differences in learning outcomes between students taught using PBL with interactive animation media and those taught using conventional methods, with the former achieving better conceptual understanding.